(untitled) (Journal of Global Arts Studies, 2024)
Background: In recent years, due to the frequent occurrence of social tragedies caused by depression, anxiety affects everyone at different times and to different degrees. Art healing, as a scientific and effective means of intervening in mental health, is quite popular among the public, and its specific fields of research cover a wide range of aspects such as psychology, art and education. Contemporary visual artists have established cooperative relationships with psychological researchers, and artworks, art venues, and artists have all established close relationships with art healing. Objective: Art festivals are not only venues for exhibiting art or creating aesthetic experiences, but also a bridge between art and society, and the collaboration between art festivals and art healing provides the public with a place of "spiritual refuge". Methods: This study analyzes the connotation of traditional art festivals, and combines it with specific examples of the Great Anxiety Festival in Australia. Results: This paper is based on the concern of art healing psychological problems, in order to examine the intervention of art on public psychological problems under the symbiosis of art festivals and art healing. Conclusion: By analyzing the collision between art and mental health in different activities of the Great Australian Anxiety Festival, we will discuss the direction of art works under the leadership of art healing and the development of future art festivals, in order to satisfy people’s growing spiritual and cultural needs.